Biogeography of Fungal Communities Associated with Pinus sylvestris L. and Picea abies (L.) H. Karst. along the Latitudinal Gradient in Europe - Valeriia Mishcherikova; Jūratė Lynikienė; Adas Marčiulynas; Artūras Gedminas; Oleh Prylutskyi; Diana Marčiulynienė; Audrius Menkis (Journal of Fungi, 2023)
We assessed the diversity and composition of fungal communities in different functional tissues and the rhizosphere soil of Pinus sylvestris and Picea abies stands along the latitudinal gradient of these tree species distributions in Europe to model possible changes in fungal communities imposed by climate change. For each tree species, living needles, shoots, roots, and the rhizosphere soil were sampled and subjected to high-throughput sequencing. Results showed that the latitude and the host tree species had a limited effect on the diversity and composition of fungal communities, which were largely explained by the environmental variables of each site and the substrate they colonize. The mean annual temperature and mean annual precipitation had a strong effect on root fungal communities, isothermality on needle fungal communities, mean temperature of the warmest quarter and precipitation of the driest month on shoot fungal communities, and precipitation seasonality on soil fungal communities. Fungal communities of both tree species are predicted to shift to habitats with a lower annual temperature amplitude and with increasing precipitation during the driest month, but the suitability of these habitats as compared to the present conditions is predicted to decrease in the future.